Analisis penggunaan media diorama berbasis QR Code terhadap hasil belajar peserta didik mata pelajaran pendidikan Pancasila - Anis Nabila; Ina Agustin; Sita Isna Malyuna (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the use of QR Code-based diorama media on student learning outcomes in the Pancasila Education map, a topok of Indonesian Social and Cultural Diversity. This study uses a mixed methods approach with a concurrent triangulation model. The research was carried out at MI Al-Ma'arif Cumpleng, Brondong District, Lamongan Regency, with 17 research subjects in grade IV. Data was obtained from test intermediaries, questionnaires, questions and answers, observations, and documentation. Quantitative data processing was analyzed from the average value and N-Gain, while qualitative data was analyzed with the Miles, Huberman, and Saldana models. Research shows that the use of QR Code-based diorama media is able to optimize student learning outcomes. The average pre-test score of 55.64 increased to 88.82 from the post-test, with an N-Gain value of 0.75 in the high category. The students' response to the use of media obtained a percentage of 93.13% in the very good category. Observations show the results of students actively observing dioramas, discussing, asking questions, and scanning QR Codes to obtain additional information. Q&A with teachers produces media that helps students to easily understand lessons, increase activity, and make the learning process more exciting. With this, diorama media with QR Code can be applied as an alternative learning media to encourage improvement of student learning outcomes.